CERITA BUDAYA DALAM PARIWISATA GASTRONOMI DI SUMATRA BARAT - Muhammad Refki Novesar; Vidya Chandra Prashanty; Ayang Khairunnisa (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to analyze the role of cultural narratives in gastronomic tourism practices in West Sumatra, particularly in shaping tourists' perceptions, experiences, and interest in visiting. A qualitative research approach was used with in-depth interviews, participatory observation, and documentation techniques. The findings of this study show that cultural narratives in Minangkabau gastronomy are socially constructed through the transmission of traditional values and institutionalized culinary practices. The context of narrative tourism has undergone strategic changes to bridge the differences in the audience's backgrounds without losing its philosophical essence. Cultural stories are conveyed through interpersonal communication and structured interpretations in tour packages, which are then contextualized by tourists. Narratives have been proven to expand the gastronomic experience from mere sensory evaluation to a holistic experience, involving emotional, educational, aesthetic, and reflective dimensions.   Keywords: Gastronomic Tourism, Cultural Stories, and West Sumatra   Abstrak: Penelitian ini bertujuan menganalisis peran cerita budaya dalam praktik pariwisata gastronomi di Sumatera Barat, khususnya dalam membentuk persepsi, pengalaman, dan minat kunjungan wisatawan. Pendekatan penelitian kualitatif dengan teknik wawancara mendalam, observasi partisipatif, dan dokumentasi. Hasil temuan dalam penelitian menunjukkan bahwa cerita budaya dalam gastronomi Minangkabau dikonstruksi secara sosial melalui transmisi nilai adat dan praktik kuliner yang terinstitusionalisasi. Konteks pariwisata narasi mengalami perubahan strategis untuk menjembatani perbedaan latar belakang wisatawan tanpa menghilangkan esensi filosofisnya. Cerita budaya disampaikan melalui komunikasi interpersonal maupun interpretasi terstruktur dalam paket wisata, yang kemudian dimaknai secara kontekstual oleh wisatawan. Narasi terbukti memperluas pengalaman gastronomi dari sekadar evaluasi sensorik menjadi pengalaman yang holistik, melibatkan dimensi emosional, edukatif, estetis, dan reflektif.   Kata kunci: Pariwisata gastronomi, Cerita Budaya, dan Sumatra Barat